THE SPATIAL REPRESENTATIONS OF CHILDREN WITH VISUAL IMPAIRMENT: PERCEPTION AND EXPERIENCES - Andrade, Leia de (Geosaberes; Vol 14 (2023)DO - 10.26895/geosaberes.v14i0.1173, 2023)
This article has the purpose to explain the perspective between Cartographic Literacy and historical-cultural theory. From the spatial concepts of location, projection, orientation and symbolization, we aim to analyze the perception of the geographic space and the place of children in their representations under daily life spaces, and enable a conception based on the historical-cultural perspective. The experiences reports allowed to list elements that are relevant in the representations of children with visual impairment emphasizing their looks and perceptions, highlighting in results that the formation of spatial concepts are socially composed by mediation and social interaction, articulated to affectivity, imagination, daily life and experiences in the geographic space.